2013
DOI: 10.1097/meg.0b013e32835d83d9
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent severe alcoholic hepatitis

Abstract: Background and aims Despite high recidivism rates in those treated for alcoholism, recurrent episodes of severe alcoholic hepatitis (SAH) have not been described. Our aim was to assess the clinical characteristics and outcomes in recurrent SAH.Patients and methods A retrospective review of patient records was carried out. Recurrent SAH was defined as two or more discrete episodes of SAH (discriminant function Z 32) coinciding with recidivism in the same patient, with documented improvement/resolution of jaundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In addition to the observation that sex/gender strongly influences immune function and the inflammatory response (Fish, 2008), previous reports have demonstrated that sex influences the biological response to EtOH (Ceylan-Isik et al, 2010). Compared to males, females exhibit: decreased risk for the development of ethanol dependence and addiction; increased ethanol sensitivity and ethanol consumption; reduced withdrawal severity; and increased risk of recidivism and relapse (Brady and Randall, 1999, Devaud and Chadda, 2001, Sershen et al, 2002, Wang et al, 2003, Carroll et al, 2004, Prescott et al, 2005, Becker and Hu, 2008, Potts et al, 2013). Evidence also indicates that ethanol is more rewarding in females (Blanchard et al, 1993, Torres et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the observation that sex/gender strongly influences immune function and the inflammatory response (Fish, 2008), previous reports have demonstrated that sex influences the biological response to EtOH (Ceylan-Isik et al, 2010). Compared to males, females exhibit: decreased risk for the development of ethanol dependence and addiction; increased ethanol sensitivity and ethanol consumption; reduced withdrawal severity; and increased risk of recidivism and relapse (Brady and Randall, 1999, Devaud and Chadda, 2001, Sershen et al, 2002, Wang et al, 2003, Carroll et al, 2004, Prescott et al, 2005, Becker and Hu, 2008, Potts et al, 2013). Evidence also indicates that ethanol is more rewarding in females (Blanchard et al, 1993, Torres et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, females have reduced levels of alcohol dehydrogenase, a key liver enzyme involved in alcohol metabolism and removal (Baraona et al, 2001). Most notably, sex differences have been characterized in numerous alcohol-related behaviors in which females show: reduced risk for the development of ethanol dependence and addiction; increased ethanol sensitivity; increased ethanol consumption; reduced withdrawal severity; and increased risk of recidivism and relapse (Brady and Randall, 1999, Devaud and Chadda, 2001, Sershen et al, 2002, Wang et al, 2003, Carroll et al, 2004, Prescott et al, 2005, Becker and Hu, 2008, Potts et al, 2013). Alcohol may also be more rewarding in females (Blanchard et al, 1993, Torres et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Mathurin et al, 2007, Pares et al, 1986) Among patients surviving the initial AH episode, patient behavior and maintenance of abstinence determines the medium- and long- term mortality. (Thursz et al, 2015, Potts et al, 2013b, Potts et al, 2013a) Recurrent AH occurs in about two thirds of survivors of the initial episode with an estimated 5 year survival of only about 32%. (Potts et al, 2013a) Recurrent AH and recidivism is more common among women, is more severe than the initial episode, and significantly impacts long-term survival.…”
Section: Resultsmentioning
confidence: 99%
“…(Potts et al, 2013a) Recurrent AH and recidivism is more common among women, is more severe than the initial episode, and significantly impacts long-term survival. (Potts et al, 2013b, Potts et al, 2013a) Studies are needed to examine reliable and accurate models predictive of recidivism so as to identify high risk groups for intervention aiming to prevent recidivism and recurrent AH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation